Asymmetric Total Synthesis and Biological Evaluation of Proapoptotic Natural Myrcene‐Derived Cyclohexenyl Chalcones. Issue 42 (17th May 2018) - Tiamas, Shelly Gapil; Audet, Florian; Samra, Alma Abou; Bignon, Jérome; Litaudon, Marc; Fourneau, Christophe; Ariffin, Azhar; Awang, Khalijah; Desrat, Sandy; Roussi, Fanny
Abstract : Based on a bioinspired asymmetric Diels–Alder cycloaddition using a chiral Evans oxazolidinone, the first total synthesis of both enantiomers of two myrcene‐derived cyclohexenyl chalcones, fislatifolione and fislatifolic acid, has been carried out. This strategy was also applied to the total synthesis of nicolaiodesin C. These natural products, as well as their synthetic intermediates, were evaluated by in‐vitro affinity displacement assays, based on the modulation of Bcl‐xL/Bak, Mcl‐1/Bid, and Bcl‐2‐Bim interactions. This study showed that (+)‐fislatifolic acid acts as a dual Bcl‐xL/Mcl‐1 inhibitor with micromolar activity, and that a Weinreb amide intermediate acts as an excellent Mcl‐1/Bcl‐2 dual inhibitor at the submicromolar level. Abstract : Based on a bioinspired asymmetric Diels–Alder cycloaddition using the Evans oxazolidinone strategy, the first total synthesis of both enantiomers of fislatifolione and fislatifolic acid has been carried out. This approach was also used for the total synthesis of nicolaiodesin C. The biological activity of these natural products, as well as their synthetic intermediates, was evaluated.